1979
DOI: 10.1007/bf01639014
|View full text |Cite
|
Sign up to set email alerts
|

Development of sulphonamide-trimethoprim combinations for urinary tract infections

Abstract: Plasma half life and in vitro activity were major criteria for selection of sulphonamides which are likely to give a strong synergistic action with trimethoprim in vivo. On the basis of literature data six sulphonamides, sulphadiazine, sulphachloropyridazine, sulphamethoxazole, sulphaisodimidine, sulphamerazine and sulphamethomidine appeared particularly suitable for combination with trimethoprim. An investigation of the activity in vitro of these compounds and their combinations with the latter against clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For this purpose, the optimal ratio between TMP and SDZ for exerting maximum synergy against target pathogens should be considered. For E. coli , Ekström, Forsgren, Örtengren, and Bergan (1979) quantified the effect of TMP and SDZ using in vitro checkerboard assays and found an optimal synergistic effect using a 1:10–1:20 ratio between TMP and SDZ. With this ratio, the MICs of these drugs in combination decreased 5.0 and 5.4 times compared to the individual MICs for TMP and SDZ, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the optimal ratio between TMP and SDZ for exerting maximum synergy against target pathogens should be considered. For E. coli , Ekström, Forsgren, Örtengren, and Bergan (1979) quantified the effect of TMP and SDZ using in vitro checkerboard assays and found an optimal synergistic effect using a 1:10–1:20 ratio between TMP and SDZ. With this ratio, the MICs of these drugs in combination decreased 5.0 and 5.4 times compared to the individual MICs for TMP and SDZ, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…is affected by the presence of an organic solvent in the injected sample. A comparison of peak heights of sulfadiazine (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) pglml) obtained from plasma samples after protein precipitation by the adopted method and from pure buffer samples, respectively, indicated that the absolute recovery from pooled plasma samples is -76%. A similar comparison of peak height ratios of sulfadiazine and sulfamerazine, the internal standard, gave congruent standard curves (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) pg/ml) from pure mobile phase and plasma, respectively, showing that the recovery of sulfamerazine from plasma is of the same magnitude as for sulfadiazine.…”
Section: Resultsmentioning
confidence: 99%